Aesthetic Comparison of Being Levels in the philosophies of Plotinus and Suhrawardi - mohammad ali sultanmoradi; yahya bouzarinejad (حکمت اسرا)
There are similarities and differences in the philosophies of Plotinus and Suhrawardi with respect to the beauty. According to Plotinus, Being has three Hypostases: (1) the One, which is the source of any beauty; the intellect, which is the greatest being; and (3) the soul. These three hypostases are originated in a hierarchical order. The philosophy of Shahab al-din Suhrawardi has its roots in the thoughts of ancient Iranian wisdom, Islamic philosophers and neoplatonic philosophy. He started the levels of being from the light of lights. Then he speaks of supreme lights. And, in the end, he talk about lights that manage the heavens and bodies. In the present paper, after a discussion about the thoughts of these two philosophers on the definition, levels and perception of beauty, we will compare the aesthetics of Light levels in Suhrawardi’s philosophy with being levels in Plotinus’s philosophy. In the end, the strengths and weaknesses of these systems will be evaluated, and we will show the relation between human beauty and perfection in Suhrawardi’s philosophy and that of Plotinus.